2016
DOI: 10.1109/ted.2016.2528218
|View full text |Cite
|
Sign up to set email alerts
|

A Stand-Alone, Physics-Based, Measurement-Driven Model and Simulation Tool for Random Telegraph Signals Originating From Experimentally Identified MOS Gate-Oxide Defects

Abstract: Investigating random telegraph signals (RTS) observed in MOS devices is important for studying the gate-oxide defect characteristics and developing simulation and modeling tools in highly scaled devices. In this paper, we are presenting a comprehensive, variable-temperature, single-to-multitrap scalable RTS model and a simulation tool (RTSSIM) based on the first principles, and supported by experimental data. The physical and electrical characteristics of the actual oxide defects are considered, such as trappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Therefore, based on the relationship 16 , 17 where T IL is the thickness of the SiO 2 interfacial layer and T HK the thickness of the HfO 2 high-k layer, ε SiO2 and ε HK are the dielectric constants for SiO 2 and the HfO 2 high-k dielectric, respectively, k B is the Boltzmann constant and T is the temperature, the vertical distance x to the oxide/channel interface can be attained. It is worth mentioning that since the RTN measurement region is above the threshold voltage in this work, the effect of ∂ψ S /∂V GS is small and thus is ignored for simplicity 18 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, based on the relationship 16 , 17 where T IL is the thickness of the SiO 2 interfacial layer and T HK the thickness of the HfO 2 high-k layer, ε SiO2 and ε HK are the dielectric constants for SiO 2 and the HfO 2 high-k dielectric, respectively, k B is the Boltzmann constant and T is the temperature, the vertical distance x to the oxide/channel interface can be attained. It is worth mentioning that since the RTN measurement region is above the threshold voltage in this work, the effect of ∂ψ S /∂V GS is small and thus is ignored for simplicity 18 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The increased number of devices per chip also leads to larger statistical spread [1,2] and high data transmission rate requires tight control of fluctuations [3]. Fluctuations have become a major concern for circuit design and have attracted many attentions recently [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It has been reported that current fluctuation in some fresh devices can be over the typical device lifetime criterion of 10% [5].…”
Section: Introductionmentioning
confidence: 99%
“…average. The discrepancy originates partly from the device-todevice variation (DDV) of relative local current density beneath a trap at Vg=Vth [16][17][18][19] and partly from the charge-induced mobility degradation [20]. Some deeply scaled devices have analyzable RTN signals in terms of extracting mean capture/emission time [11], while others can have a complex within-a-device-fluctuation [12].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many efforts to model RTN, both in the frequency domain [1], [19]- [21] and in the time domain [1]- [6]. It is widely accepted that RTN originates from trapping/detrapping charge carriers from/to the conduction channel [1]- [21]. The number of traps per device follows the Poisson distribution [3]- [6].…”
Section: Introductionmentioning
confidence: 99%